2011
DOI: 10.1177/1077559511402048
|View full text |Cite
|
Sign up to set email alerts
|

Change Trajectories During Home-Based Services With Chronic Child Welfare Cases

Abstract: This study examines how risk factor change patterns vary with case chronicity, and whether risk factor improvement still predicts lower recidivism risk among chronic cases. 2,175 parents in home based child welfare services were surveyed for risk factors at pre-treatment, post-treatment and 6-month follow-up. Mixture modeling of latent difference scores identified change trajectory classes related retrospectively to chronicity and prospectively to recidivism. Five change trajectories were identified: stable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…However, families of children in the Elevated Severity class, specifically those families with subsequent substantiated maltreatment reports, do not seem to respond to provided services, or possibly the amount or quality of services these families receive is insufficient. This class is consistent with previous research indicating that chronic cases with high problem levels often show limited improvement during service provision (Chaffin, Bard, Hecht, & Silovsky, 2011). At the same time, these cases might raise additional concern among teachers and counselors, which in turn leads to an increased number of unsubstantiated reports.…”
Section: Discussionsupporting
confidence: 92%
“…However, families of children in the Elevated Severity class, specifically those families with subsequent substantiated maltreatment reports, do not seem to respond to provided services, or possibly the amount or quality of services these families receive is insufficient. This class is consistent with previous research indicating that chronic cases with high problem levels often show limited improvement during service provision (Chaffin, Bard, Hecht, & Silovsky, 2011). At the same time, these cases might raise additional concern among teachers and counselors, which in turn leads to an increased number of unsubstantiated reports.…”
Section: Discussionsupporting
confidence: 92%
“…These benefits may be more clear in families with psychiatric problems, because they meet needs related to deficits in parenting control behaviors (Johnston et al, 2012 ) as well as higher levels of stress (Johnston & Mash, 2001 ). A study on chronic problems of FMP also reported that approaches that emphasize monitoring may be more suitable for these families (Chaffin et al, 2011 ). A greater intensity of telephone contacts to support and monitor the family between visits therefore seems valuable for reaching more positive outcomes in FMP.…”
Section: Discussionmentioning
confidence: 99%
“…The act of viewing parental functioning and the child–parent relationship in contextual terms could provide more possibilities of treatment and intervention. For example, if the discussion of parental fitness incorporated factors such as “poverty” (Drake and Jonson-Reid, 2014; Kotchick and Forehand, 2002), “parental stress” (Cicchetti and Lynch, 1993; Herrenkohl and Herrenkohl, 2007), “multi-problem family” (Chaffin et al., 2011; Jonson-Reid et al., 2010); social support, processes of change and interactions between the child and the parents as well as between the parents and the environment (Sperry and Widom, 2013; Spilsbury and Korbin, 2013), this would lead to a broader understanding of problematic situations and enable different approaches to family interventions.…”
Section: Discussionmentioning
confidence: 99%